Seismic performance of a 3D full-scale high-ductile steel?concrete composite moment-resisting frame?Part II Test results and analytical validation. - Braconi, A. (Earthquake engineering & structural dynamics.)
This paper presents the results of a multi-level pseudo-dynamic seismic test program that was performed to assess the performance of a full-scale three-bay, two-storey steel?concrete composite moment-resisting frame built with partially encased composite columns and partial-strength beam-to-column joints. The system was designed to develop a ductile response in the joint components of beam-to-column joints including flexural yielding of beam end plates and shear yielding of the column web panel zone. The ground motion producing the damageability limit state interstorey drift caused minor damage while the ultimate limit state ground motion level entailed column web panel yielding, connection yielding and plastic hinging at the column base connections. The earthquake level chosen to approach the collapse limit state induced more damage and was accompanied by further column web panel yielding, connection yielding and inelastic phenomena at column base connections without local buckling. During the final quasi-static cyclic test with stepwise increasing displacement?amplitudes up to an interstorey drift angle of 4.6%, the behaviour was ductile although cracking of beam-to-end-plate welds was observed. Correlations with numerical simulations taking into account the inelastic cyclic response of beam-to-column and column base joints are also presented in the paper together. Inelastic static pushover and time history analysis procedures are used to estimate the structural behaviour and overstrength factors of the structural system under study.